Effects of technological cooperation on the innovative activity of the colombian manufacturing sector - Castillo-Molina, Yury Yohana; Gómez-Villamarín, Cesar Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The purpose of this research was to analyze the effect that technological cooperation with business partners and knowledge organizations, both national and foreign, has on the development of technological and non-technological innovation in companies in the Colombian manufacturing sector. A research with a quantitative approach was carried out, in which secondary information from 1.845 manufacturing companies was used, collected in the IX survey of Technological Development and Innovation of Colombia. The results indicate that cooperation with national companies has a greater effect on product and process innovation, while cooperation with national knowledge organizations contributes more to organizational innovation. It is also found that market innovation is not influenced by any type of cooperation, and that international cooperation has no effect on any type of innovation. It is concluded that the types of innovation have different determinants that favor their achievement, therefore, the decision to carry out technological cooperation must start from the definition of the business strategy and the knowledge of the contribution that each type of partner can make to it.